The influence of organizational culture and competency on employee performance - Zulki Zulkifli Noor (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Performance is a key factor for every individual and organization in achieving productivity Organizations do not only pursue the achievement of high productivity, but also pay more attention to performance in the process of achieving it. This study aims to examine the effect of Organizational Culture and Competency on Employee Performance. This study uses explanatory quantitative research on 40 distributor company in DKI Jakarta with 75 respondents processed using the SEM-PLS approach. Based on result study, it can be seen that organizational culture has a partial effect on employee performance, which means that the more often employees comfort with their organizational culture, the higher their performance in the organization. Then, competency has an effect on employee performance, which means that the more compentence, the higher the employee's performance.